(untitled) (Revista de Estudos da Linguagem, 2005)
This study focuses on hybridization and ambivalence of genresand discourses that emerge in late modernity narratives. The workis based on critical discourse analysis, which views language as ahistorically marked social activity. The results of the article pointto the relation among discourse, genre and social change.